THE IMPLEMENTATION OF THE SUSPECT'S RIGHTS IN THE LEGALITY OF PRETRIAL INVESTIGATION - Budiyanto Budiyanto; Farida Kaplele; Alwan Hadiyanto (UNISSULA, 2023)
The purpose of this study is examine the legality of the investigative process at pretrial hearings and their constraints. The normative legal research method supported by empirical legal research is used in this study. The results of the study found that the suspect's right to test the legality of the investigation process at the pretrial hearing has been implemented through legal procedures in accordance with the provisions of Article 77, Article 79, Article 82 and Article 95 of the Criminal Procedure Code. In its implementation, out of a total of 40 cases, 15 cases were rejected, 7 cases were granted, 7 cases were withdrawn, 4 cases could not be accepted, 6 cases were declared disqualified, 1 case was still in trial. As a result, it was found that there were procedural errors and violations of rights committed by investigators, so that during the examination the pretrial hearing was declared invalid. Obstacles for a legality test for the investigation process through a pretrial hearing include: the pretrial request was declared invalid, declared unacceptable, the difficulty for the suspect to find legal counsel who could win his case, the high cost of paying attorneys, the suspect's ignorance and ignorance of legal issues.